An approach: reducing annealing time of optical stimulated luminescence dosimeter (OSLD) for medical application purpose - Omar, Ratna Suffhiyanni; Hashim, Suhairul; Ghoshal, Sib Krishna; Musa, Yahaya; Hashim, Asmaliza; Abdul Karim, Muhammad Khalis (2018)
For single point dose measurements, the use of optically stimulated luminescence dosimeters (OSLDs), nanoDots is gaining a remarkable interest due to availability and potential attributes. In this paper, new methods to optically anneal the nanoDot™ OSLDs were developed using five different light source namely; 40 W purple ultra-violet light (UV), 5 W white light-emitting diode (LED), 100 W tungsten-halogen lamp (THL), 14 W compact fluorescent lamp (CFL) and bright room office environment light (BRL) having steady temperatures of 35 ºC, 25 ºC, 30 ºC, 27 ºC and 24 ºC respectively, while the OSL system performance was evaluated via intrinsic measurements to ascertain the precision of the microStar reader. The reader stability evaluated from the dark current (DRK), CAL and LED counts were found to be 6.0 ± 0.9, 1677 ± 31, and 4657 ± 563, respectively, which were rightly below the control limits of 30 (DRK), and ±10% of the mean (CAL and LED). The regeneration rate of the OSL signal during the optical annealing procedure revealed that 14 W CFL (Compact Fluorescent Lamp) gives the highest response with an average signal loss of ~93% in 60 minutes illumination time, compared to 92%, 90%, 87% and 44% signal loss using UV light, LED, THL, and BRL, respectively. Two useful output were produced using this method; (i) periodic output constancy introduced by variation of sensitivity among different nanoDot™ OSL dosimeters, and (ii) reduced the annealing time when using the pocket annealer (which only can only anneal one dosimeter at a time).